Quantitative factorization of weakly compact, Rosenthal, and $ξ$-Banach-Saks operators - Beanland, Kevin; Causey, Ryan M. (MATHEMATICA SCANDINAVICA, 2018)
We prove quantitative factorization results for several classes of operators, including weakly compact, Rosenthal, and ξ-Banach-Saks operators.